PEMERTAHANAN BAHASA SUNDA SEBAGAI ALAT KOMUNIKASI OLEH PENUTUR SUNDA DI KOMPLEKS PERUMAHAN DI KABUPATEN BANDUNG - NFN Wagiati; Duddy Zein (Balai Bahasa Kalimantan Tengah, 2017)
This study describes the maintenance of the Sundanese language as a means of communication by speakers living in residences in Bandung Regency. The method used is qualitative method with descriptive data analysis. The analysis is divided into six domains of communication, namely kinship, neighborhood, intimacy, education, transaction, and government. The result of the research shows that (1) Sundanese is often used by Sundanese speakers in residential complex in Bandung in four communication domains, namely kinship, intimacy, neighborhood, and transaction. It means that the maintenance of Sundanese language in all four domains is still quite strong. In the realm of education and government, the maintenance of Sundanese language is very weak. (2) The interlocutor factor is crucial to the decision of the use of Sundanese language in the realm of communication. In the realm of education, there are non-Sundanese students who still maintain their mother tongue. This condition continues to grow until finally the number of students speaking Sundanese as their mother tongue decrease in number. In the realm of transaction, the interlocutor factor is also crucial. Sundanese is used by Sundanese speakers if the interlocutor is clearly identified as Sundanese. If it is not recognized, the Indonesian language will be used. Younger speakers also use Indonesian more when dealing with officials in government offices, including village head offices, some of whom are Sundanese and speak one